Cover Picture: Rhodium Nanoflowers Stabilized by a Nitrogen‐Rich PEG‐Tagged Substrate as Recyclable Catalyst for the Stereoselective Hydrosilylation of Internal Alkynes (Adv. Synth. Catal. 1/2015). Issue 1 (12th January 2015) - Guo, Wusheng; Pleixats, Roser; Shafir, Alexandr; Parella, Teodor
<x xml:space="preserve">Abstract</x> The front cover picture, provided by Pleixats, Shafir and co‐authors, illustrates the stereoselective hydrosilylation of internal alkynes catalyzed by flower‐shaped rhodium nanoparticles prepared in water using a nitrogen‐rich stabilizer. The method provides nearly quantitative yields of a wide range of vinylsilanes using 0.5 mol% Rh both under solvent‐free conditions (neat silane) and in solution. The pure product is obtained after a simple extraction with Et2O, and the catalyst was recycled up to six times. The exceptional air‐ and water‐tolerance of the new system was traced to the reluctance of the Rh nanoflowers to catalyze the hydrolytic oxidation of the SiH bond. Details can be found in the full paper on pages 89–99 (W. Guo, R. Pleixats, A. Shafir, T. Parella, Adv. Synth. Catal. 2015, 357, 89–99; DOI: 10.1002/adsc.201400740).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>